PELATIHAN INSTALASI PENERANGAN SEL SURYA DI PEMANDIAN SUMBERWRINGIN - Mohamad Rifai; Guntur Yanuar Astono; Isac Ilham Akbar Habibi; Miftakhul Huda; Achmad Komarudin; Herman Hariyadi (Jurnal Pengabdian kepada Masyarakat, 2023)
Wringinsongo Village is one of Polinema's partner villages. Wringinsongo Village is located in Tumpang District. There is a lot of potential in Wriginsongo Village, including potential, fishery plantations, agriculture, and water resources. The local government of Malang Regency through Wringin Songo Village reads the situation as an opportunity to improve the welfare of its citizens. So that currently the spring functions as water tourism called Sumberwringin Baths which is managed by the village government as an attractive natural recreation facility. Sumberwringin bathhouse is a potential bathhouse to be developed by Wringin Songo village, but this bath is still lacking in terms of lighting. The manager wants to install lighting around the baths by utilizing natural resources, namely sunlight. Therefore, training in the use of sunlight (PLTS) for lighting and training on the maintenance of solar power plant equipment is needed